2022
DOI: 10.1108/pr-05-2021-0330
|View full text |Cite
|
Sign up to set email alerts
|

A moderated mediation model of counterproductive work behaviour, organisational justice, organisational embeddedness and psychological ownership

Abstract: PurposeThis study aimed to investigate the mechanisms through which organisational justice influences counterproductive work behaviour (CWB). This relationship was explained using a moderated mediation model where organisational embeddedness is a mediator between organisational justice and CWB, while psychological ownership (for the organisation) is a moderator of the relationship between organisational embeddedness and CWB. The conservation of resources (COR) theory was used as the underpinning theory to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
(155 reference statements)
0
9
0
Order By: Relevance
“…We posit that these sub-themes denote different forms of workplace ostracism that alone or in combination act as sources of deteriorated belongingness and inclusion at work. 11,12,13,15 This description resembles previously suggested definitions of ostracism, such as that of stating that workplace ostracism denotes acts of omission and open exclusionary behavior that "hinders one's ability to establish or maintain positive interpersonal relationships, work-related success, or favorable reputation" at work . 17,19 However, it also offers a more precise account of the behavioral aspects of ostracism apparent when enacted by an immediate leader.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We posit that these sub-themes denote different forms of workplace ostracism that alone or in combination act as sources of deteriorated belongingness and inclusion at work. 11,12,13,15 This description resembles previously suggested definitions of ostracism, such as that of stating that workplace ostracism denotes acts of omission and open exclusionary behavior that "hinders one's ability to establish or maintain positive interpersonal relationships, work-related success, or favorable reputation" at work . 17,19 However, it also offers a more precise account of the behavioral aspects of ostracism apparent when enacted by an immediate leader.…”
Section: Discussionmentioning
confidence: 86%
“…Investigate the association between workplace ostracism and counterproductive work behaviors as well as the underlying personal and situational contributing factors. 10,11 Many researchers further in their studies were provided a direction to health care organizations towards investing in training and development of their employees regarding effective management of their emotions with theoretical and practical perspectives thereby, strengthening the basic abilities and skills of employees to express reasonable conduct which can leads to improve work performance. 15,16,17 Supporting above evidence another qualitative study findings were quoted, that depicting that ostracism ends up in defensive silences, passes through the exhaustion stage, and promotes social deviances.…”
Section: Introductionmentioning
confidence: 99%
“…Psychologically empowered employees are more likely to work for the betterment of their organizations even in a stressful environment; therefore, management is suggested to offer interventions to enhance employees’ psychological empowerment. This can be achieved through systematic changes in the organization, tolerating, carrying (Ghani et al , 2020), providing autonomy to control their schedules, participation in decision-making and delegating controls (Mehmood et al , 2022). At the same time, management should adopt positive leadership because a negative leadership can reduce employees’ psychological empowerment (Liu et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the research has shown that perception of justice influence attitudes, thoughts, emotions, and behaviors in the organization. Previous studies have found that CWB is influenced by numerous factors; however, organizational justice has been found to be a consistent predictor (Mehmood et al, 2023). According to the equity hypothesis developed by Al-A'wasa (2018) exposing employees unfair treatment make employee feel dissatisfied with organization.…”
Section: Organizational Justice and Counterproductive Work Behaviormentioning
confidence: 99%